Islamic Republic of Iran : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues Paper on Iran reviews that monetary factors are the main determinants of inflation in the country. Government spending out of oil revenues leads to large liquidity injections that the central bank accommodates owing to its efforts to prevent a significant nominal appreciation of the rial and the lack of effective sterilization instruments. The growing discontent with inflation, however, has compelled policymakers to focus on this issue, bringing it to the forefront of the policy agenda.